Управление проектами обратного инжиниринга - Иванов, В. В. (НТУ "ХПИ", 2015)
Расширено понятие обратного инжиниринга и предложено его подразделение на три класса: концептуальный, агрегатный и полный. Дан анализ состава команды проекта, оборудования, программного обеспечения и эвристических методов применяемых для каждого из классов. Показано использование эвристических методов при концептуальном обратном инжиниринге.

It is extended the concept of reverse engineering and invited its division into three classes of problems: conceptual, aggregate and complete. The analysis of the composition of the project team, the hardware, software and heuristic methods are used in each of the classes is made. The use of heuristic methods for reverse engineering concept is showed.
Project management of reverse engineering
Keywords: эвристические методы; команда проекта; модель процесса исполнения; ремонт оборудования; reverse engineering; heuristic methods; project team; generalized method of studying; structure of the problem